(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The issue of child labor has been a significant issue everywhere on the world, country, area and in a general public. The quantity of children labor has been expanding in our nation and the quantity of child individuals is more in our nation when contrasted with some other nation on the planet. This is likewise a major issue in the state of Haryana. Because of lack of education, obliviousness, conventional reasoning, neediness and ignorance are the fundamental reasons of child labor. Children from poor and uneducated families work to make money. Neediness is one of the primary explanations behind separation, influencing individuals’ admittance to approach treatment including administrations, for example, wellbeing and training. The children age under 14 years have working in different fields like tea slows down, cloth pickers and dish washers in dhabas. Numerous arrangements are given in our Constitution and Law to control child labor however financial conditions predominant in the nation don’t confront children to get necessary instruction and to appreciate right to training. The endeavor has been made in this paper to give brief record of the reasons of child labor in Haryana and recommendations to control child labor. This investigation inferred that The Government of Haryana needs to execute enactment supporting the Indian Child Labor Act.